2015
DOI: 10.1107/s1600576715012765
|View full text |Cite
|
Sign up to set email alerts
|

In situmonitoring of phase transformation microstructures at Earth's mantle pressure and temperature using multi-grain XRD

Abstract: Microstructures govern the mechanical properties of materials and change dramatically during phase transformations. A detailed understanding of microstructures at different stages of a transformation is important for the design of new materials and for constraining geophysical processes. However, experimental studies of transformation microstructures at the grain scale have been mostly based on ex situ observations of quenched products, which are difficult to correlate with bulk sample properties and transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 38 publications
(28 reference statements)
3
22
0
Order By: Relevance
“…Microstructure evolution with time in (a, c, and e) Experiment #3 [ Rosa et al , ] and (b, d, f, and g) Experiment #4 (this study). (Figures a and b) Volume fraction of phases ( α , β , and γ ( * ) ).…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…Microstructure evolution with time in (a, c, and e) Experiment #3 [ Rosa et al , ] and (b, d, f, and g) Experiment #4 (this study). (Figures a and b) Volume fraction of phases ( α , β , and γ ( * ) ).…”
Section: Resultsmentioning
confidence: 59%
“…Table summarizes the P / T conditions and observations of all experiments. Experiments #1–#3 are from Rosa et al , . Experiments #4–#6 are new.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the multigrain method (Sørensen et al 2012) has been successfully applied to study coarse-grained polycrystalline samples obtained under ultra-high P-T conditions in a DAC (Nisr et al 2012;Zhang et al 2013;Zhang et al 2014;Rosa et al 2015;Zhang et al 2016). These studies have demonstrated that integration of the multigrain method with synchrotron XRD is suitable for treating each sub-micron-sized crystallite as a single crystal in a coarse-grained polycrystalline material in a DAC.…”
Section: Introductionmentioning
confidence: 99%